1979
DOI: 10.1002/pssa.2210530115
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer study of the effect of alloying elements on the carbide phase in cold-worked steel

Abstract: The effect of the alloying elements on the cementite decomposition during the steel plastic deformation is studied by means of the NGR technique. The decomposition is shown to be governed by the competition between the binding energy of the carbon atoms to the dislocations in ferrite and the cementite solution heat. Among the elements under consideration vanadium and nickel suppress the cementite decomposition most effectively. The alloying elements distribution among the G‐ and S‐sites of the cementite lattic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 6 publications
1
9
1
Order By: Relevance
“…[16][17][18][19][20] Such dissolution of q during cold drawing was also pointed out by means of Mössbauer spectroscopy. 3,[21][22][23] In fact, the present authors also observed the nanocrystalline q formed by heavy cold rolling. 2) Thus, the strain hardening of pearlite structure cannot be simply explained by the refining of ISP.…”
Section: The Strengthening Of Pearlite By Cold Rollingmentioning
confidence: 65%
See 1 more Smart Citation
“…[16][17][18][19][20] Such dissolution of q during cold drawing was also pointed out by means of Mössbauer spectroscopy. 3,[21][22][23] In fact, the present authors also observed the nanocrystalline q formed by heavy cold rolling. 2) Thus, the strain hardening of pearlite structure cannot be simply explained by the refining of ISP.…”
Section: The Strengthening Of Pearlite By Cold Rollingmentioning
confidence: 65%
“…19) A Mössbauer study on the alloying effect on the q dissolution shows that the amount of dissolution changes depending on the third alloying element. 21) For example, Mn favors the q dissolution whereas Si does not influence noticeably. However, a further study is necessary to examine the dissolution of q in the alloyed pearlite by cold deformation.…”
Section: The Strengthening Of Pearlite By Cold Rollingmentioning
confidence: 99%
“…This indicates that the alloying elements Ni and Cr would decrease the dissolution rate of lamellar cementite during wire drawing. The delayed occurrence of delamination due to the addition of Ni is well explained by Gavrilyuk [22]. A remarkable decrease in the binding enthalpy between carbon atoms and dislocations diminishes the effect of cementite decomposition.…”
Section: Effect Of Alloying Elements On the Occurrence Of Delaminationmentioning
confidence: 96%
“…According to Gavrilyuk [21,22], the addition of alloying elements to pearlitic steels affects the decomposition of cementite during wire drawing by changing the interatomic bonds in cementite and the binding enthalpy between carbon atoms and dislocations in ferrite.…”
Section: Effect Of Alloying Elements On the Occurrence Of Delaminationmentioning
confidence: 99%
“…Accordingly, the decomposition of the cementite may possibly reduce the RA of the drawn steel wires. The degree of cementite decomposition during the wire drawing depends on the deformability of the lamellar cementite, which is influenced by the chemical compositions of steels [22] in addition to the initial interlamellar spacing [23]. The strong binding energy between the Cr and carbon atoms may likely delay the decomposition of cementite during the wire drawing.…”
Section: Ductility Of Cold Drawn Wiresmentioning
confidence: 99%